Exploitation and conservation of fish genetic resources in Africa: Issues and priorities for aquaculture development and research - Lind, C.E.; Brummett, R.E.; Ponzoni, R.W. (Wiley, 2012)
Africa harbours a rich biological diversity of native fish resources. Recognition of the potential to use these resources to make significant contributions towards improving African food security through aquaculture has existed for some time. A key challenge, however, is achieving compatibility between the two urgent, but sometimes conflicting, goals of reducing poverty and food insecurity in Africa through aquaculture development while paying due attention to the conservation of natural biodiversity and fish genetic resources (FiGR). In this paper we highlight the overarching challenges concerning the conservation and exploitation of FiGR for the long-term development of aquaculture for food production in Africa. We address the major issues requiring attention in genetic improvement programs in order to take full advantage of the highly diverse wild FiGR in Africa, and we expand on strategies such as zoning, environmental risk analysis and molecular characterization approaches that can be used to minimize the potential harm to wild FiGR arising from aquaculture activities and future development. Finally, we discuss the challenge of strengthening local capacity. The enhancement of local capacity is essential because it will enable the fundamental link required to achieve the desired outcome of increasing the productivity of aquatic animals for food in Africa in a sustainable manner. We trust that this paper will provide a good basis for an in-depth discussion of the subject, as well as guidance on future research and development priorities for the compatible exploitation and conservation of FiGR in Africa.